Bank dan Riba: Implikasinya dalam Ekonomi Islam - Buhari, A. Taufiq (LPPPM STAI Darul Hikmah Bangkalan, 2020)
Islamic banks are banks whose activities leave usury problems. While usury is meant is excess property in a muamalah with no compensation. The mechanism of interest-free Islamic banking / usury based on philosophical and practical reasons. The principle of Islamic banking profit sharing makes the risk of loss smaller than deposit interest, but this high profit share still cannot provide a large influence on the economy. The reason is people still choose bank interest because the negative implications of the bank interest system are not felt directly individually in the near future by the public